Portuguese children’s exposure to second-hand tobacco smoke in the family car - Vitória, PD (2015)
Objectives: To assess the prevalence of children's exposure to second-hand smoke in the family car; to compare exposure among children with smoking and non-smoking parents. Methods: In 2011, a self-administered questionnaire was applied to a 4th grade Portuguese children national sample (N=3187, mean age 9.5±0.7, 51.1% boys). Prevalence rates and chi-square tests were computed. Results: Of the participants, 52.0% reported having, at least, one smoking parent. Overall exposure in the car was 28.9% (95% CI 27.3-30.5). Children's exposure among those reporting smoking parents was 46.9% (95% CI 44.4-49.4); and 8.6% (95% CI 7.1-10.1) among those reporting non-smoking parents (p<.001). Therefore, children with smoking parents were 5.44 times more likely to be exposed. Conclusions: Children's exposure to second-hand smoke in the family car is frequent, especially if one or both parents smoke. This highlights the need for effective tobacco control measures to prevent this severe health hazard.